2017
DOI: 10.9790/2402-1104017480
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Evaluation of River Owan Water for Irrigation

Abstract: Water samples from River Owan located within the Benin-Owena River Basin, southwestern Nigeria, were investigated for irrigation suitability employing electrical conductivity (EC), Sodium Absorption Ratio (SAR), %Na, Residual Sodium Bicarbonate (RSBC), Potential Salinity (PS), Soluble Sodium Product (SSP), Magnesium absorption ratio (MAR), Kelly ratio (KR) and Wilcox plot. Estimated irrigation parameters revealed that SAR ranged from 0. RSBC; MAR; KR; while PS, SSP and %Na were from 0. 01 -3.12 (av. 0.56),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…In terms of KR, all values were lower than 1, indicating that the water is suitable for irrigation as mentioned by [10] (Figure 13). PS values, which influenced by Cl and SO 4, were higher than 3 (Figure 14), indicating that the water is not suitable for irrigation [5]. However, PI as indicator of soil permeability which affected by the watering for long durations and the concentration of Na, Ca, HCO 3 and Mg in the soil.…”
Section: Other Parametersmentioning
confidence: 98%
See 3 more Smart Citations
“…In terms of KR, all values were lower than 1, indicating that the water is suitable for irrigation as mentioned by [10] (Figure 13). PS values, which influenced by Cl and SO 4, were higher than 3 (Figure 14), indicating that the water is not suitable for irrigation [5]. However, PI as indicator of soil permeability which affected by the watering for long durations and the concentration of Na, Ca, HCO 3 and Mg in the soil.…”
Section: Other Parametersmentioning
confidence: 98%
“…According to Food and Agricultural Organization (FAO) limits [10], SAR problem is low in the study area during the wet season, as all values were less than 10. Based on the US salinity diagram that is used to evaluate the rate of infiltration according to SAR and EC values [4,5], all samples in this work were within the class C4-S2, which indicated that the water of Garmat Ali river is characterized by high salinity and low sodium. Therefore, its acceptable for watering any type of soil, and only the plants that adapted with high levels of salinity.…”
Section: Infiltration Hazardmentioning
confidence: 99%
See 2 more Smart Citations
“…A equação 11 apresenta o equacionamento do índice. O Índice de Kelly é voltado para avaliar como as trocas iônicas entre Na+, Mg2+ e Ca2+ podem afetar cultivos(TALABI et al, 2017). A formulação matemática do índice está descrita na Equação 12.…”
unclassified